USE OF RENEWABLE ENERGY SOURCES (American Journal of Interdisciplinary Research and Development, 2023)
Some drawbacks of using traditional non-renewable resources to generate electricity include environmental pollution and depletion of natural resources. Wind power can generate clean energy without emitting greenhouse gases, but it requires sufficient wind to generate electricity, and production completely stops when there is no wind. Solar power relies on the sun and produces free and sustainable energy, but the initial cost is high. Hydropower is a clean source of energy but can negatively impact fish populations and biodiversity. Geothermal power is clean and sustainable, but it is only viable in specific locations and has environmental risks. Switching to renewable energy is crucial for reducing our carbon footprints and creating sustainable economies.